Sustainable Rural Development through Tourism - SAYABAEV, Kaisar; ZHOLMUKHANOVA, Aigul; NUKESHEVA, Anar; TLEUZHANOVA, Danagul; ASSILOV, Bakhyt; ZHANSAGIMOVA, Ayagoz (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).25, 2020)
The status of the capital suburb gives additional attractiveness to rural territories for both internal migrants and labor migrants from other regions and oblasts of the country. Social and economic problems are the factor of strengthening the migratory activity of the population of able-bodied age that can have a considerable influence on changing the demographic situation. The population shift is one of the global processes in the modern world. At present virtually all countries are faced with this phenomenon in various forms depending on the level of social and economic development, geographical location and specifics of the proceeding demographic processes. Shchuchinsko-Borovskaya resort area is a resort with excellent natural and climatic conditions, rich therapeutic and recreational resources and historical and cultural foundation, favorable geographical location in the center of the Republic, close to the capital of the Republic of Kazakhstan, Astana. The growth of the income of travel agencies can be expected due to the increase in the cost of the package, because the number of vouchers is likely to decrease due to the reduction of potential tourists. Given that the strategy of long-term development of the Akmola region provides state stimulation of tourism development and recreation in the region, it will be necessary to improve the information and statistical support of this area.